A case of strangulated intestinal obstruction due to ileo-ileal true knot: Peculiar computed tomography findings - Isamu Saeki; Ryo Touge; Masato Kojima; Sho Kurihara; Chihiro Tani (Elsevier, 2023)
Background: Nodule formation of the intestine is a rare disease, and the ileo-ileal type is extremely rare. We herein report a pediatric case of strangulated intestinal obstruction due to an ileo-ileal true knot. Case presentation: A 9-year-old boy with no medical history was referred to our hospital complaining of sudden-onset abdominal pain. An emergent laparotomy was performed under the diagnosis of strangulated intestinal obstruction. Two intestinal loops formed a true knot. After releasing the strangulation, resection of the necrotic intestine and intestinal anastomosis were performed, and the post-operative course was uneventful. On a retrospective examination of computed tomography findings, a particular S-shaped whirl sign was recognized as a feature of imaging findings. Conclusions: This is the youngest case report of ileo-ileal true knot in Japan. The S-shaped whirl sign may be an imaging feature of the disease.